Proceedings of the Thirtieth Annual ACM-SIAM Symposium on Discrete Algorithms 2019
DOI: 10.1137/1.9781611975482.149
|View full text |Cite
|
Sign up to set email alerts
|

Lower Bounds for Oblivious Data Structures

Abstract: An oblivious data structure is a data structure where the memory access patterns reveals no information about the operations performed on it. Such data structures were introduced by Wang et al. [ACM SIGSAC'14] and are intended for situations where one wishes to store the data structure at an untrusted server. One way to obtain an oblivious data structure is simply to run a classic data structure on an oblivious RAM (ORAM). Until very recently, this resulted in an overhead of ω(lg n) for the most natural sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 45 publications
(45 reference statements)
0
10
0
Order By: Relevance
“…Optimality. Path Oblivious Heap outperforms existing works both in asymptotic and concrete performance, and moreover achieves optimality in light of the recent lower bound by Jacob et al [24]. We recommend the Path-variant for a cloud outsourcing scenario, and the Circuit-variant for RAM-model multi-party computation [23], [30] -recall that these are the two primary application scenarios for oblivious algorithms.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Optimality. Path Oblivious Heap outperforms existing works both in asymptotic and concrete performance, and moreover achieves optimality in light of the recent lower bound by Jacob et al [24]. We recommend the Path-variant for a cloud outsourcing scenario, and the Circuit-variant for RAM-model multi-party computation [23], [30] -recall that these are the two primary application scenarios for oblivious algorithms.…”
Section: Introductionmentioning
confidence: 80%
“…The very recent work of Jafargholi et al [25] was first to answer this question affirmatively: they showed how to construct an oblivious priority queue where each request completes in amortized O(log N ) bandwidth, but requiring O(log 1 δ ) words of CPU cache. In another very recent work, Jacob et al [24] prove that any oblivious priority queue must incur Ω(log N ) bandwidth per request even when the CPU can store O(N ) words in its private cache where 0 < < 1 is an arbitrary constant.…”
Section: B Related Workmentioning
confidence: 99%
“…The seminal work of Larsen and Nielsen [LN18] presented the first cell-probe lower bound for oblivious data structures, in which they proved a (tight) Ω(lg n) lower bound for ORAMs. Jacob et al [JLN19] show Ω(lg n) cell-probe lower bounds for oblivious stacks, queues, deques, priority queues and search trees. Both [LN18, JLN19] adapt the information transfer technique of Pǎtraşcu and Demaine [PD06].…”
Section: Related Workmentioning
confidence: 99%
“…For the problem of RAMs, it has been shown that the Θ(lg n) overhead is both necessary and sufficient [LN18,PY19]. Jacob et al [JLN19] also show that the Θ(lg n) overhead is necessary and sufficient for many fundamental data structures such as stacks and queues, but quite surprisingly, Jafargholi et al [JLS19] very recently showed that (comparison-based) priority queues can be made oblivious with no overhead at all. We consider this question for the ANN problem.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation